UPAYA PENANGGULANGAN TINDAK PIDANA PENIPUAN SITUS JUAL BELI ONLINE DI INDONESIA - Jevlin Solim; Mazmur Septian Rumapea; Agung Wijaya; Bella Monica Manurung; Wendy Lionggodinata (Fakultas Hukum, Universitas Samudra, 2019)
E-commerce website transaction offers lots of benefit and convenience to its users. On the other hand, this electronic transaction raises legal issues, one of those is fraud. Therefore, to minimalize this issue further research regarding legal arrangements, types, and prevention need to be conducted. The method of this research is normative juridicial. The result of this research shows that there are various types of fraud exist in e-commerce websites. Nevertheless, Indonesia has legalized regulations and enacted laws concerning fraud in e-commerce. In addition, government, police, and e-commerce website providers have both educated and developed policies to protect its users and minimalize fraud that possibly happen at e-commerce websites.